Practical UMAC algorithm on hybrid crypto-code constructions of McElise on shortened MEC - Havrylova, A. (My University, 2019)
A study was carried out on the use of an improved UMAC algorithm in post-quantum cryptography based on the formation of a substrate on the third layer of the hash code generation by the McElise crypto-code system on elliptic codes. The paper considers a practical algorithm for generating a hash code based on an example implementation of a cascading UMAC hash algorithm with the McElise crypto-code construction on elliptic codes. Using a hybrid crypto-code design allows you to save the universality of the hash code at the output of the algorithm, which allows its use in large databases as an identifier. In addition, in the context of the implementation of a full-scale quantum computer, US NIST experts consider crypto-code systems as one of the effective post-quantum cryptography algorithms. This approach allows you to implement the UMAC modification on various modifications of hybrid crypto-code structures and to ensure the formation of authentication profiles of different strength and length.
Keywords: UMAC hashing algorithm; McElice hybrid crypto code constructions; elliptic codes